Supplementation of Rumen By Pass Protein-Fat: Effect on Feed Intake, Nutrient Digestibility and The Profile of Duodenal Digesta Fatty Acids - Hartati, Lilis; Sumantri, Ika; Agus, Ali (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2014)
Abstract. The aim of this research was to study the effects of rumen by pass protein-fat supplementation (RBPF) on feed intake, nutrients digestibility and profile of duodenal digesta of fatty acids. Two rumen fistulated and duodenum canulated dairy cows were fed ration that consisted of king grass and concentrate (60:40). The concentrate was supplemented with 20% RBPF. The feeding trial was conducted for four weeks in which the first week was the control period, the second week was the adaptation period, the third week was the early collection period and finally the fourth week was the late collection period. The samples of duodenal digesta were collected 1 hour before morning feeding and 1, 3 and 5 hours after morning feeding. The cows were fed twice a day and concentrate was offered before forage. The results showed that in comparison to the control, supplementation of RBPF increased nutrients intake of dry matter (DM) (6.95 vs. 6.27%), organic matter (OM) (6.20 vs. 5.70%), crude fat (CF) (0.49 vs. 0.41%), crude fiber (CFb) (1.84 vs. 1.49%) and nitrogen free extract (NFE) (3.23 vs. 3.03%), while the crude protein (CP) intake decreased (0.64 vs. 0.77%). Supplementation of RBPF improved the nutrients digestibility of dry matter (67.24 vs. 62.15%), organic matter (68.71 vs. 65.29%), crude fiber (66.20 vs. 57.46%) and nitrogen free extract (72.37 vs. 66.47%). RBPF supplementation also increased linoleic acid content in duodenal digesta sample at 1and 3 hours after feeding. In conclusion, RBPF supplementation did not negatively affect feed intake and nutrient digestibility. RBPF also increased the proportion of linolenic acid, eicosapentaenoic acid (EPA) and docosahexsaenoic acid (DHA) in duodenal digesta until 3 hours after feeding. Key words: RBPF, supplementation, feed intake, nutrient digestibility, fatty acid Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh suplementasi protein-lemak by pass rumen terhadap konsumsi, kecernaan nutrien serta profil asam lemak pada digesta duodenum sapi perah. Dua ekor sapi perah berfistula rumen dan berkanula duodenum diberi pakan hijauan dan konsentrat dengan rasio 60:40, diberi suplemen protein-lemak by pass rumen 20% dari konsentrat. Percobaan dilakukan selama 4 minggu, minggu pertama adalah periode kontrol, minggu ke-2 periode adaptasi, minggu ke-3 periode koleksi awal dan minggu ke-4 periode koleksi akhir. Sampel digesta duodenum diambil 1 jam sebelum pemberian pakan dan 1; 3 serta 5 jam setelah pemberian pakan. Ransum diberikan dua kali sehari dengan konsentrat lebih dulu sebelum hijauan. Dibanding periode kontrol, suplementasi protein lemak by pass rumen sebanyak 20% menaikkan konsumsi bahan kering (BK) (6,95 vs 6,27%), bahan organik (BO) (6,20 vs 5,70%), lemak kasar (LK) (0,49 vs 0,41%), serat kasar (SK) (1,84 vs 1,49%) dan bahan ekstrak tanpa nitrogen (BETN) (3,23 vs 3,03%) tetapi menurunkan konsumsi protein kasar (PK) (0,64 vs 0,77%). Suplementasi protein lemak by pass rumen juga memberikan kecernaan BK, BO, SK dan BETN ( 67,24 vs 62,15%; 68,71 vs 65,29%; 66,20 vs 57,46%; 72,37 vs 66,47%) yang lebih tinggi dibanding kontrol. Suplementasi lemak by pass rumen juga menaikkan proporsi asam lemak linolenat pada jam ke-1 dan ke-3 setelah makan. Pemberian protein-lemak by pass rumen dalam ransum tidak berpengaruh negatif terhadap konsumsi dan kecernaan nutrien pakan serta meningkatkan proporsi asam lemak linoleat, EPA (eicosapentaenoic acid) dan DHA (docosahexsaenoic acid) digesta duodenum. Kata kunci: protein lemak by pass rumen, suplementasi, konsumsi, kecernaan nutrien, asam lemak